MO996COVID-19 IN RENAL TRANSPLANT RECIPIENTS; A CASE SERIES FROM IRAQ. (29th May 2021) - Ali, Ala; S. Klaif, Mohammed; Altaee, Huda
Abstract: Background and Aims: Renal transplant recipients seems at particular risk for Coronavirus disease 2019 (COVID‐19). In addition to immune suppression cessation, multiple therapies have been tried with no supportive evidence. Favipiravir and colchicine showed benefit in some reports. Here we describe 19 adult renal transplant recipients with mild to moderate COVID-19 who were treated with the cessation of immunosuppression, favipiravir, and colchicine on an outpatient basis. Results: This case series includes 19 renal transplant recipients with a mean age of 38.4 + 11.6 years and a mean duration of 55.9 + 36.1 months post-transplant. They were maintained on triple therapy with a calcineurine inhibitor, antiproliferative therapy and steroids. The laboratory data at weeks 1, 2, and 3 showed that at weeks 2 all markers of inflammation increased especially serum ferritin (1718 + 315 ng/ml). Serum creatinine increased by < 30% with urine protein creatinine of < 500 mg/g. The mean time to recovery was 13 + 3.1 days. The patient who was on mTOR inhibitor showed the highest inflammatory response and the longest time to recovery, 18 days. All patients showed complete recovery with stable graft function and no patient warranted dialysis, nor ICU care. Conclusion: In the settings of limited resources, unavailability of costly immunomodulatory therapies and limited hospital capacity, early case definition, judicious management of immune suppression, and affordable antiviral and anti-inflammatory drugs will improve outcome in early cases of COVID-19 in renal transplant recipients.